2009
DOI: 10.1590/s0102-311x2009000500021
|View full text |Cite
|
Sign up to set email alerts
|

Fatores de risco para diabetes mellitus gestacional na coorte de nascimentos de Pelotas, Rio Grande do Sul, Brasil, 2004

Abstract: Consensus statements by various countries have reported age, obesity, and family history of diabetes mellitus as risk factors for gestational diabetes mellitus. Other factors remain controversial. The aim of this study was to investigate factors associated with gestational diabetes among mothers of newborns from the birth cohort in Pelotas, Rio Grande do Sul State, Brazil, in 2004. We interviewed 4,243 postpartum women in hospital, with a 0.5% refusal rate. Diagnosis of gestational diabetes was self-reported. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0
5

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(34 citation statements)
references
References 36 publications
1
28
0
5
Order By: Relevance
“…When limited to studies that presented adjusted analyses (4 studies), the odds ratio was 0.95 (95% CI 0.85–1.07, 4 studies). Since the publication of this review article, three studies have found no association [1921] between smoking and GDM risk while 2 retrospective studies and one prospective study reported a protective effect of smoking on GDM risk [22, 23]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When limited to studies that presented adjusted analyses (4 studies), the odds ratio was 0.95 (95% CI 0.85–1.07, 4 studies). Since the publication of this review article, three studies have found no association [1921] between smoking and GDM risk while 2 retrospective studies and one prospective study reported a protective effect of smoking on GDM risk [22, 23]. …”
Section: Discussionmentioning
confidence: 99%
“…When the analysis was stratified by parity, there was a stronger protective effect among nulliparous women (OR 0.31, 95% CI 0.13–0.75). Based on postpartum interviews of smoking status, Dode and Santos noted a protective effect of first (OR 0.40, 95% CI 0.20–0.79) and second trimester (OR 0.43, 95% CI 0.21–0.87) smoking on GDM risk [23]. Similarly, we observed that women who smoked during pregnancy had an unadjusted OR of 0.46 (95% CI 0.22, 0.95); however this effect was attenuated in multivariable analyses and no longer statistically significant.…”
Section: Discussionmentioning
confidence: 99%
“…Pregnancy over the age 35 is configured in an increasingly common reality observed nowadays, being related to changes in lifestyle; in which women postpone pregnancy over professional and personal goals. In this context, the gestational diabetes mellitus is characterized as a disease associated with advanced maternal age condition, but researchers warn that age cannot be analyzed in isolation, other important factors, such as obesity and family history may be present in younger women (7)(8) .…”
Section: Discussionmentioning
confidence: 99%
“…Um estudo para determinar a prevalência de DMG em grávidas atendidas em Unidades Básicas de Saúde da cidade de Vitória/ES concluiu que essa taxa foi de 5,8% em uma amostra de 396 gestantes 6 . Em outro estudo realizado em Pelotas/RS, que investigou os fatores associados à ocorrência de DMG em 4.243 puérperas, a prevalência dessa patologia foi de 2,95% 7 . As taxas anteriormente citadas demonstram a relevância do DMG, tanto como uma intercorrência adquirida no decorrer da gravidez, quanto como um problema de saúde pública.…”
Section: Implications Of Diet Restrictions In the Daily Lives Of Womeunclassified